The systemic risk of corporate credit securitization revisited - Benjamin Lojak; Thomas Theobald (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
We develop a stock-flow-consistent macroeconomic model with an agent-based focus on corporate credit markets, including a securitization process. Against the background of increased corporate indebtedness, our interest is in quantifying contagion effects that endogenously arise from corporate defaults in a securitized credit portfolio. We calibrate the model to the U.S., where corporate credit securitization has been reintensified in recent years. Simulations deliver adverse medium- to long-term effects as soon as the share of securitized loans in total new loans economy-wide approaches 10%. Securitization activities above this threshold lead to significant welfare losses from the medium-term onwards. Two transmission channels are conceivable. A collapsing special purpose vehicle (SPV) either causes distortions in the banking sector or increases liquidity constraints that ultimately dampen households' consumption due to their financial investment in the securitized tranches. A more concentrated banking sector reinforces the adverse shock of a liquidation of the SPV. In contrast, a faster and better-equipped bank rescue mechanism in the form of levies within the banking sector helps to contain the consequences of a SPV collapse.
urn:nbn:de:101:1-2020071014255247361785
Keywords: E03; G21; G23; 330; securitization; systemic risk; agent-based; stock-flow consistent